Grain-oriented electrical steel sheet and method for producing grain-oriented electrical steel sheet
By controlling the local heating of the laser beam and the oxygen potential during the decarburization annealing process, the problems of uneven magnetic flux density and coating adhesion in directional electromagnetic steel sheets were solved, achieving a combination of high magnetic flux density and excellent coating adhesion.
Patent Information
- Application Number
- CN202480024071.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-12
- Filing Date
- 2024-04-11
- Publication Date
- 2025-11-04
AI Technical Summary
In the existing technology, directional electromagnetic steel plates have problems with uneven magnetic flux density and film adhesion, especially in the rapid heating decarburization annealing process, which can easily lead to deterioration of magnetic properties and reduced film adhesion.
By precisely controlling the local heating of the laser beam and the oxygen potential during the decarburization annealing process, a periodically decreasing region of oxygen intensity distribution is formed, and Gaussian-oriented grains are enriched on the surface of the steel plate, suppressing {211} <011> The secondary recrystallization of oriented grains simultaneously promotes the formation of an internal oxide layer in SiO2 to improve the adhesion of the film.
It achieves an excellent combination of magnetic properties and coating adhesion, ensuring high magnetic flux density and stability of directional electromagnetic steel plates, while avoiding a reduction in coating adhesion.
Smart Images

Figure CN120898017A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a grain-oriented magnetic steel sheet and a method for manufacturing a grain-oriented magnetic steel sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2023-065018 filed on April 12, 2023, and the content thereof is hereby incorporated by reference. BACKGROUND
[0003] A grain-oriented magnetic steel sheet is a soft magnetic material, and is mainly used as a core material for a transformer. Therefore, for a grain-oriented magnetic steel sheet, high magnetization characteristics and low iron loss, which are magnetic characteristics, are required. The so-called iron loss refers to electric power loss consumed as heat energy in the case where a core is excited with an alternating magnetic field, and from the viewpoint of energy saving, it is required to be as low as possible.
[0004] The iron loss is represented by the sum of a hysteresis loss depending on crystal orientation, purity, and the like, and an eddy current loss depending on sheet thickness, resistivity, size of magnetic domains, and the like. Therefore, in order to reduce the iron loss, it is effective to reduce the hysteresis loss and to reduce the eddy current loss. As a method for reducing the hysteresis loss, there is known a method of increasing the magnetic flux density by gathering crystal orientation in a Goss orientation ({110} <001> orientation) which has good magnetic characteristics (increasing orientation gather degree). In addition, as a method for reducing the eddy current loss, there are known a method of increasing the content of Si which increases the resistance, a method of reducing the sheet thickness of the steel sheet, and a method of refining the magnetic domains.
[0005] In particular, in the method of reducing the sheet thickness, cold rolling is mostly used. However, in the case of a grain-oriented magnetic steel sheet having a thin sheet thickness, there is a problem that good magnetic characteristics cannot be stably obtained. As a method for improving the magnetic characteristics of a grain-oriented magnetic steel sheet having a thin sheet thickness, for example, the following technology is disclosed.
[0006] In Patent Literature 1, a method for manufacturing a grain-oriented magnetic steel sheet is disclosed, which performs two cold rollings with intermediate annealing in between. Specifically, in Patent Literature 1, the following is disclosed: after hot rolling is finished at 850°C or higher, immediately cooling and coiling at 600°C or lower, before the first cold rolling, performing carbide adjustment heat treatment of soaking for 2 to 10 seconds in a temperature range of 650 to 900°C. Thereby, even in the case of a grain-oriented magnetic steel sheet having a thin sheet thickness, excellent magnetic flux density can be stably obtained in the length direction of the coil.
[0007] Patent Document 2 discloses a method for manufacturing directional electromagnetic steel sheets, which involves one cold rolling or two or more cold rolling processes with intermediate annealing. Specifically, Patent Document 2 discloses that by setting the final cold rolling reduction rate to 89% or more, and heating the strip rolled to the final sheet thickness to a temperature of 700°C or more at a heating rate of 50°C / s or more just before decarburization annealing, excellent magnetic flux density and iron loss are obtained.
[0008] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 6-145799 Patent Document 2: Japanese Patent Application Publication No. 7-62438 Summary of the Invention
[0009] The problem that the invention aims to solve However, in conventional techniques, uneven magnetic flux density may occur. In addition, when rapid heating occurs during the decarburization annealing process, the adhesion between the steel plate and the insulating film (hereinafter referred to as film adhesion) may decrease.
[0010] The purpose of this disclosure is to provide a directional electromagnetic steel sheet with excellent magnetic properties and coating adhesion, and a method for manufacturing the same.
[0011] Methods for solving problems The main points of this disclosure are as follows.
[0012] [1] One embodiment of the present disclosure is a directional electromagnetic steel plate comprising a base steel plate, a primary coating formed on the base steel plate, and a secondary coating formed on the primary coating. The chemical composition of the base steel plate, expressed as a percentage by mass, contains: Si: 2.50~4.00% Mn: 0.01~0.30%, N: 0.0001~0.0100% C: 0.0005~0.010% sol.Al: 0~0.010%, Selected from one or more of S and Se: totaling 0 to 0.010%. Ti: 0.001~0.010%, Ni: 0~0.50%, Cu: 0~0.50%, Sb: 0~0.30%, Sn: 0~0.30% Cr: 0–0.50% P: 0–0.05%, Mo: 0–0.05%, Ta: 0~0.05%, Nb: 0~0.010%, V: 0~0.50%, B: 0~0.010% Bi: 0~0.0150%, and Te: 0~0.0150%, The remaining portion contains Fe and impurities. The magnetic flux density B8 is above 1.902T. When X-ray diffraction-based crystal orientation measurement points are arranged at 6mm intervals on the surface of the base steel plate in both the rolling direction and in directions orthogonal to the rolling direction, with {211} <011> The proportion of measurement points with an orientation difference within 15° relative to all measurement points is less than 5%. In the oxygen intensity profile of the primary coating surface obtained by line analysis along the rolling direction using an electron beam microscope, there are periodically occurring regions of decreased oxygen intensity. The minimum oxygen intensity Io in the oxygen intensity reduction region min The maximum oxygen intensity Io in the region outside the oxygen intensity reduction region. max The ratio of Io min / Io max The value ranges from 0.85 to 0.96.
[0013] [2] According to the directional electromagnetic steel plate described in [1] above, the oxygen intensity reduction region may also exist at intervals L of 5 to 30 mm.
[0014] [3] According to the directional electromagnetic steel sheet described in [1] or [2] above, the chemical composition of the base steel sheet may also contain one or more elements selected from the following elements in mass percent: Ni: 0.01~0.50%, Cu: 0.01~0.50%, Sb: 0.01~0.30% Sn: 0.01~0.30% Cr: 0.01~0.50% P: 0.01~0.05%, Mo: 0.01–0.05% Ta: 0.01~0.05%, Nb: 0.001~0.010%, V: 0.01~0.50%, B: 0.001~0.010% Bi: below 0.0100%, and Te: below 0.0100%.
[0015] [4] The thickness of the directional electromagnetic steel plate according to any one of [1] to [3] above may also be 0.15 to 0.23 mm.
[0016] [5] The directional electromagnetic steel plate according to any one of [1] to [4] above, wherein the thickness of the base steel plate may also be 0.14 to 0.22 mm.
[0017] [6] One embodiment of the present disclosure has a method for manufacturing a directional electromagnetic steel plate comprising the following steps: A hot rolling process involves heating a slab and then hot rolling the heated slab to produce a hot-rolled steel plate. The slab contains, by weight percent: Si: 2.50~4.00% Mn: 0.01~0.30%, N: 0.0030~0.0150% C: 0.010~0.100% sol.Al: 0.010~0.050%, Selected from one or more of S and Se: total 0.010–0.050%, Ti: 0.001–0.010%. Ni: 0~0.50%, Cu: 0~0.50%, Sb: 0~0.30%, Sn: 0~0.30% Cr: 0–0.50% P: 0–0.05%, Mo: 0–0.05%, Ta: 0~0.05%, Nb: 0~0.010%, V: 0~0.50%, B: 0~0.010% Bi: 0~0.0200%, and Te: 0~0.0200%, The remaining portion contains Fe and impurities; The hot-rolled steel sheet is annealed using a hot-rolled sheet annealing process. The cold rolling process involves cold rolling the hot-rolled steel sheet after the annealing process to produce a cold-rolled steel sheet. The decarburizing annealing process of decarburizing annealing the cold-rolled steel sheet to produce decarburized annealed steel sheet; The finished annealing process involves coating the decarburized annealed steel sheet with an annealing separating agent and then performing finished annealing to form a primary coating on the surface of the decarburized annealed steel sheet, thereby producing a finished annealed sheet; and The insulating film forming process involves forming an insulating film on the surface of the finished annealed plate. The total reduction rate in the cold rolling process is over 89%. The decarburization annealing process includes the following steps: A localized heating process in which the surface of the cold-rolled steel sheet is partially heated in an atmospheric atmosphere by laser beam irradiation at intervals of 5 to 30 mm in a direction at an angle of 30 to 150° relative to the rolling direction. The process of heating the cold-rolled steel sheet after the local heating process in a non-oxidizing atmosphere at an average heating rate of 80°C / s to 2000°C / s from a temperature range below 450°C to a decarburization annealing temperature range of 750 to 950°C; and The cold-rolled steel sheet after the heating process is subjected to an oxygen potential P that satisfies the following formula (1). O The homogenization process is carried out for decarburization annealing. Under the irradiation conditions of the laser beam during the local heating process, the average intensity of the laser beam, expressed in W, is set as P; the focusing diameter of the focused spot in the rolling direction, expressed in mm, is set as Dl; the focusing diameter of the focused spot in the width direction orthogonal to the rolling direction, expressed in mm, is set as Dc; the irradiation time, expressed in sec, is set as t; and the instantaneous input energy, expressed as 4 / π×P / (Dl×Dc)×t, is set as J / mm². 2 When the setting is Up, the following equation (2) is satisfied.
[0018] P O ≤0.6-0.04Up (1) 1≤Up≤5 (2)。
[0019] [7] In the method for manufacturing directional electromagnetic steel sheet according to [6] above, the chemical composition of the slab may also contain one or more elements selected from the following elements in mass percent: Ni: 0.01~0.50%, Cu: 0.01~0.50%, Sb: 0.01~0.30% Sn: 0.01~0.30% Cr: 0.01~0.50% P: 0.01~0.05%, Mo: 0.01–0.05% Ta: 0.01~0.05%, Nb: 0.001~0.010%, V: 0.01~0.50%, B: 0.001~0.010% Bi: below 0.0100%, and Te: below 0.0100%.
[0020] Invention Effects According to this disclosure, a directional electromagnetic steel sheet with excellent magnetic properties and coating adhesion, and a method for manufacturing the same, are provided. Attached Figure Description
[0021] Figure 1 This is a diagram showing an example of a cold-rolled steel sheet with a wire-shaped heating section.
[0022] Figure 2 It is a diagram used to illustrate the focusing diameter and scanning speed of a laser beam.
[0023] Figure 3 This is a schematic diagram of the oxygen intensity distribution measured by linear analysis of the film surface using EPMA. Detailed Implementation
[0024] <1. Research conducted by the inventors of this invention> The following describes one embodiment of the present invention. First, the research conducted by the inventors of the present invention will be described. The inventors of the present invention investigated the causes of the deterioration and unevenness of magnetic flux density in directional electromagnetic steel sheets. As a result, the deterioration of magnetic properties is caused by {211} <011> This is caused by secondary recrystallization of grains with poor magnetic properties due to their crystalline orientation. Furthermore, it was determined that the magnetic properties become uneven along the length of the roll, with significant degradation at the ends of the roll.
[0025] {211} <011> The reason for the secondary recrystallization of oriented grains at the ends of the roll material along its length is unclear, but speculation is made as follows.
[0026] The ends of the coil along its length may be heated above the desired temperature during hot rolling. In these overheated areas, decarburization is more likely to occur on the surface of the steel sheet during hot rolling. If decarburization occurs on the surface of the steel sheet, the austenite ratio during hot rolling decreases, resulting in a rolling-stable orientation of ferrite {211} on the surface of the steel sheet. <011> Orientation becomes easier to develop. It is speculated that: {211} <011> The orientation is inherited and further developed even after cold rolling, resulting in the formation of a large number of {211} <011> Oriented secondary recrystallized grains (hereinafter also referred to as "{211}") <011> Secondary recrystallized grains). In particular, it is speculated that in the case of directional electromagnetic steel sheets manufactured with a high cold rolling rate, {211} developed during hot rolling. <011> Orientation is more easily inherited during cold rolling.
[0027] As mentioned above, the {211} <011> Secondary recrystallization of grains is a major factor contributing to the deterioration of magnetic properties. Therefore, the inventors of this invention have made efforts to suppress {211} <011> The methods for forming secondary recrystallized grains have been studied in depth.
[0028] First, regarding {211} <011> The reasons why secondary recrystallization of oriented grains becomes easier were investigated, and the following is presumed to be one of the reasons: Gaussian orientation that becomes the nucleus for secondary recrystallization ({110}). <001> Orientation) decreases. In particular, it is believed that when manufacturing directional electromagnetic steel sheets with high cold rolling reduction rates, the reduction of Gaussian orientation leads to {211} <011> Secondary recrystallization of oriented grains becomes easier.
[0029] Therefore, methods for enriching Gaussian orientations were investigated.
[0030] As a method for enriching Gaussian orientation, a technique of rapid heating during the decarburization annealing process is known. However, in directional electromagnetic steel sheets, {211} may have poor magnetic properties. <011> Secondary recrystallization of oriented grains can result in poor magnetic properties or produce uneven magnetic properties.
[0031] Against this background, the inventors of this invention have focused on further refining the rapid heating process during the heating phase of the decarburization annealing process. As a result, it has been discovered that performing precise control of the irradiation conditions for localized rapid heating based on a laser beam, along with control of the oxygen potential in the decarburization annealing process conforming to these laser beam irradiation conditions, together helps to suppress {211} <011> Secondary recrystallization of oriented grains is effective.
[0032] In conventional heating methods such as radiation heating, electrothermal heating, and induction heating, the heating rate is increased during the annealing process to enrich Gaussian-oriented grains, which serve as nuclei for secondary recrystallization. On the other hand, in these conventional heating methods, Gaussian-oriented grain growth is promoted at the center of the steel plate along its thickness direction. <112> There is a tendency for the nearby orientation grains to decrease, and there is a limit to the improvement in magnetic properties brought about by increasing the heating rate in the annealing process. In particular, in thin directional electromagnetic steel sheets, the reduction of Gaussian orientation grains, which become nuclei for secondary recrystallization grains, is a problem. However, in the application of conventional heating methods, since the entire sheet thickness is heated, sufficient results have not been obtained for the reasons mentioned above.
[0033] On the other hand, localized rapid heating based on laser beams, because it rapidly heats only the surface layer of the steel plate (especially 1 / 5 of the thickness), can enrich Gaussian-oriented grains, which will become nuclei for secondary recrystallization, on the surface layer of the steel plate, and suppress {111} in the center of the steel plate thickness. <112> The reduction of nearby oriented grains. Therefore, it can promote the secondary recrystallization of Gaussian oriented grains with excellent magnetic properties.
[0034] However, the inventors of this invention investigated the relationship between the laser beam irradiation conditions and various properties of the electromagnetic steel sheet, and determined that there was a situation where the coating adhesion deteriorated. Specifically, the research showed that the annealing conditions (especially the homogenization conditions) in the decarburization annealing process affected the coating adhesion, and that controlling the laser beam irradiation conditions together with the annealing conditions within an appropriate range was effective in improving the coating adhesion.
[0035] The decrease in film adhesion is caused by the reduction of the primary film, namely the forsterite (Mg2SiO4) film, at the laser beam irradiation site. The reason for the reduction of the primary film at the laser beam irradiation site is unclear, but it is believed that: at the laser beam irradiation site, it is difficult to form the SiO2 internal oxide layer in the decarburization annealing process, and in the finished product annealing process, which is a subsequent process, the amount of primary film formed is locally reduced.
[0036] Therefore, in order to promote the formation of the internal oxide layer of SiO2 at the laser beam irradiation area, the inventors of this invention conducted an in-depth investigation into the annealing conditions in the decarburization annealing process. The results showed that suppressing the oxygen potential during the homogenization process of the decarburization annealing process in conjunction with the laser beam irradiation conditions is effective in promoting the formation of the internal oxide layer of SiO2. This is believed to be because by suppressing the oxygen potential during the homogenization process to a lower level, the overall oxygen adhesion of the steel plate is reduced, but in the laser beam irradiation area, the formation of the internal oxide layer of SiO2 is promoted, rather than the formation of an iron-based oxide layer.
[0037] The following is a detailed description of a directional electromagnetic steel plate and its manufacturing method according to one embodiment of the present invention, which was completed based on the above knowledge.
[0038] <2. Manufacturing Method of Directional Electromagnetic Steel Sheet> First, a method for manufacturing a directional electromagnetic steel plate according to one embodiment of the present disclosure (the method for manufacturing a directional electromagnetic steel plate according to this embodiment) will be described.
[0039] The manufacturing method of the directional electromagnetic steel plate of this embodiment includes the following steps.
[0040] (I) A hot rolling process in which a slab having a specified chemical composition is heated and the heated slab is hot rolled to produce a hot-rolled steel plate; (II) The hot-rolled steel sheet annealing process of annealing the above-mentioned hot-rolled steel sheet; (III) A cold rolling process in which the hot-rolled steel sheet after the above-mentioned hot-rolled sheet annealing process is subjected to cold rolling to produce a cold-rolled steel sheet; (IV) The decarburizing annealing process for producing decarburized annealed steel sheets by decarburizing the above-mentioned cold-rolled steel sheets; and (V) Finished annealing process for the above-mentioned decarburized annealed steel sheet.
[0041] The following describes each process step. For processes or conditions not described, well-known processes and conditions may be applied.
[0042] (Hot rolling process) In the hot rolling process, a slab with the chemical composition described later is heated to above 1280°C, and the heated slab is hot rolled to produce a hot-rolled steel plate.
[0043] If the heating temperature is below 1280°C, inclusions formed in the slab cannot be dissolved, and inhibitors cannot be sufficiently formed in the hot rolling and hot-rolled annealing processes described later. Therefore, the heating temperature of the slab is set to 1280°C or higher. There is no upper limit to the slab heating temperature, but if heating exceeds 1450°C, the slab melts, making hot rolling difficult. Therefore, the slab heating temperature is preferably below 1450°C.
[0044] There are no particular limitations on the hot rolling conditions; they can be set appropriately based on the required characteristics. The thickness of the hot-rolled steel sheet obtained by hot rolling is preferably in the range of 1.0 mm to 4.0 mm.
[0045] [Chemical composition of the slab] To obtain the preferred magnetic properties for directional electromagnetic steel sheets, the chemical composition of the hot-rolled slab is set within the following range. In the following description, unless otherwise specified, "%" indicates "mass %". Furthermore, the lower and upper limits of the numerical ranges enclosed in "~" are included within these ranges. Values expressed as "lower than" or "higher than" are not included within the numerical ranges.
[0046] C: 0.010~0.100% Carbon (C) is an element that indicates the improvement effect on magnetic flux density. However, when the C content in the slab exceeds 0.100%, the productivity of the decarburization annealing process decreases. Furthermore, with a high C content and insufficient decarburization in the slab, the steel undergoes a phase transformation during secondary recrystallization annealing (i.e., finished product annealing), but secondary recrystallization is insufficient, resulting in poor magnetic flux density and low iron loss, or deterioration of magnetic properties due to magnetic aging. Therefore, the C content in the slab is set to 0.100% or less. The lower the C content, the better for productivity and iron loss reduction. From the viewpoint of productivity and iron loss reduction, the C content is preferably 0.090% or less, and more preferably 0.080% or less.
[0047] On the other hand, when the carbon content of the slab is less than 0.010%, the improvement in magnetic flux density cannot be obtained. Therefore, the carbon content of the slab is set to 0.010% or more. The carbon content is preferably 0.040% or more, and more preferably 0.060% or more.
[0048] Si: 2.50~4.00% Silicon (Si) is an extremely effective element for increasing the resistivity of steel, thereby reducing eddy current losses, which constitute part of iron losses. When the Si content in the slab is below 2.50%, the resistivity is low, and eddy current losses cannot be sufficiently reduced. Furthermore, during secondary recrystallization annealing, the steel undergoes a phase transformation, and secondary recrystallization is not sufficient, resulting in poor magnetic flux density and low iron losses. Therefore, the Si content in the slab is set to 2.50% or more. Preferably, the Si content in the slab is 2.70% or more, and more preferably 2.80% or more.
[0049] On the other hand, when the Si content exceeds 4.00%, the steel sheet becomes brittle, and the permeability during manufacturing is significantly deteriorated. Therefore, the Si content of the slab is set to 4.00% or less. Preferably, the Si content of the slab is 3.90% or less, and more preferably 3.80% or less.
[0050] Mn: 0.01~0.30% Manganese (Mn) is an important element in the formation of MnS, which is one of the main inhibitors of MnS formation. When the Mn content in the slab is less than 0.01%, the absolute amount of MnS required for secondary recrystallization is insufficient. Therefore, the Mn content in the slab is set to be 0.01% or more. The Mn content is preferably 0.03% or more, and more preferably 0.06% or more.
[0051] On the other hand, when the Mn content in the slab exceeds 0.30%, the steel undergoes a phase transformation during secondary recrystallization annealing, but secondary recrystallization will not be fully carried out, resulting in poor magnetic flux density and low iron loss.
[0052] Therefore, the Mn content of the slab is set to 0.30% or less. The Mn content is preferably 0.28% or less, and more preferably 0.26% or less.
[0053] Selected from one or more of S and Se: 0.010–0.050% Sulfur (S) and selenium (Se) are elements that react with Mn to form MnS and MnSe, which act as inhibitors. Since the formation of MnS or MnSe as inhibitors is sufficient, the slab can contain one or both of S and Se. If the total content of one or both of S and Se is less than 0.010%, sufficient inhibitors will not be formed. Therefore, the total content of one or both of S and Se is set to 0.010% or more. The total content of one or both of S and Se is preferably 0.020% or more. On the other hand, if the total content of one or both of S and Se exceeds 0.050%, it becomes a cause of hot brittleness, making hot rolling significantly difficult. Therefore, the total content of one or both of S and Se is set to 0.050% or less. The total content of one or both of S and Se is preferably 0.040% or less, more preferably 0.030% or less.
[0054] sol.Al: 0.010~0.050% Sol.Al (acid-soluble aluminum) is a major constituent element of compounds known as inhibitors in the secondary recrystallization of directional electromagnetic steel sheets. In the base steel sheet of this embodiment, it is an essential element from the viewpoint of exhibiting secondary recrystallization. When the sol.Al content in the slab is less than 0.010%, AlN, which functions as an inhibitor, is not sufficiently generated, and secondary recrystallization becomes insufficient. Therefore, the sol.Al content is set to 0.010% or more. The sol.Al content is preferably 0.020% or more. On the other hand, when the sol.Al content exceeds 0.050%, AlN, which functions as an inhibitor, is not sufficiently generated, and secondary recrystallization becomes insufficient. Therefore, the sol.Al content is set to 0.050% or less. The sol.Al content is preferably 0.040% or less, and more preferably 0.030% or less.
[0055] N: 0.0030~0.0150% Nitrogen (N) is an element that reacts with the acid-soluble Al described above to form AlN, which functions as an inhibitor. To ensure sufficient formation of AlN as an inhibitor, the N content is set to 0.0030% or more. Preferably, the N content is 0.0050% or more.
[0056] On the other hand, when the nitrogen content exceeds 0.0150%, bubbles (voids) are generated in the steel sheet during cold rolling, and the strength of the steel sheet increases while the sheet's permeability deteriorates during manufacturing. Therefore, the nitrogen content of the slab is set to 0.0150% or less. The nitrogen content is preferably 0.0130% or less, and more preferably 0.0100% or less.
[0057] Ni: 0~0.50% Ni (Ni) is an effective element for increasing electrical resistance and thus reducing iron loss. Furthermore, Ni is effective in controlling the microstructure of hot-rolled steel sheets and improving magnetic properties. Therefore, Ni may be included. To achieve the above effects, the Ni content is preferably set to 0.01% or more. More preferably, the Ni content is 0.02% or more.
[0058] On the other hand, if the Ni content exceeds 0.50%, secondary recrystallization may become unstable. Therefore, the Ni content is set to 0.50% or less. Preferably, the Ni content is 0.30% or less.
[0059] Cu: 0~0.50% Cu (copper) is an element that contributes to increasing the Gaussian orientation occupancy in the secondary recrystallization structure and improves the adhesion of the glass film. Therefore, Cu may be included. To obtain the above-mentioned effects, it is preferable to set the Cu content to 0.01% or more. More preferably, the Cu content is 0.02% or more, and even more preferably 0.03% or more.
[0060] On the other hand, when the Cu content exceeds 0.50%, the steel sheet becomes brittle during hot rolling. Therefore, the Cu content of the slab is set to 0.50% or less. The Cu content is preferably 0.30% or less, and more preferably 0.10% or less.
[0061] Sb: 0~0.30% Antimony (Sb) is an element that improves magnetic properties. Therefore, it may be present in a container. When Sb is present, it is preferable to set the content to 0.01% or more to maximize the improvement in magnetic properties. More preferably, the Sb content is 0.02% or more.
[0062] On the other hand, if the Sb content exceeds 0.30%, the adhesion of the glass coating deteriorates. Therefore, the Sb content is set to 0.30% or less. Preferably, the Sb content is 0.20% or less.
[0063] Sn: 0~0.30% Sn (tin) is an element that improves magnetic properties. Therefore, Sn can be included. When Sn is included, it is preferable to set the Sn content to 0.01% or more in order to fully exert the effect of improving magnetic properties. If both magnetic properties and film adhesion are considered, the Sn content is preferably 0.02% or more, and more preferably 0.03% or more.
[0064] On the other hand, if the Sn content exceeds 0.30%, the glass coating deteriorates significantly, and sufficient tension is not obtained for magnetic domain refinement, thus deteriorating the iron loss characteristics. Therefore, the Sn content is set to 0.30% or less. The Sn content is preferably 0.20% or less, and more preferably 0.15% or less.
[0065] Cr: 0~0.50% Cr (chromium) is an element that, like Sn and Cu described later, contributes to increasing the Gaussian orientation occupancy in the secondary recrystallization structure, thereby improving magnetic properties and enhancing the adhesion of the glass film. Therefore, Cr may also be included. To obtain the above effects, it is preferable to set the Cr content to 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more.
[0066] On the other hand, when the Cr content exceeds 0.50%, Cr oxide is formed, which reduces the magnetic properties. Therefore, the Cr content is set to 0.50% or less. The Cr content is preferably 0.30% or less, and more preferably 0.10% or less.
[0067] P: 0–0.05% Phosphorus (P) is an element that reduces workability during rolling. By setting the P content to 0.05% or less, excessive reduction in rolling workability can be prevented, and breakage during manufacturing can be suppressed. From this point of view, the P content is set to 0.05% or less. The P content is preferably 0.04% or less.
[0068] There is no lower limit to the phosphorus (P) content; it can be as low as 0%. However, P is also an element that can improve texture and magnetic properties. To achieve this effect, the P content can be set to 0.005% or higher, or 0.01% or higher.
[0069] Mo: 0–0.05% Mo (molybdenum) is an element that improves magnetic properties. Therefore, it may be present in the composition of a metal. When Mo is present, to maximize the improvement in magnetic properties, it is preferable to set the Mo content to 0.01% or more. More preferably, the Mo content is 0.02% or more, and even more preferably 0.03% or more.
[0070] On the other hand, if the Mo content exceeds 0.05%, cold rollability may deteriorate, leading to breakage. Therefore, the Mo content is set to 0.05% or less. Preferably, the Mo content is 0.04% or less.
[0071] Ta: 0~0.05% Ta (tantalum) is a useful element that functions as an inhibitor by combining with N and C. To achieve this effect, the Ta content can be set to more than 0.0000% or more than 0.0005%. On the other hand, if the Ta content exceeds 0.05%, the magnetic properties may decrease. Therefore, the Ta content only needs to be 0.05% or less. The Ta content is preferably 0.04% or less.
[0072] Nb: 0~0.010% Niobium (Nb) has the function of stabilizing secondary recrystallization. To achieve the above effect, the Nb content can be set to more than 0.0000% or more than 0.0005%. On the other hand, if the Nb content exceeds 0.010%, secondary recrystallization may become unstable. Therefore, the Nb content only needs to be 0.010% or less. The Nb content is preferably 0.0050% or less.
[0073] V: 0~0.50% Vanadium (V) is an effective element that combines with nitrogen (N) and carbon (C) to function as an inhibitor. Therefore, it may also contain V. To achieve the above-mentioned effects, the V content is preferably 0.01% or more, more preferably 0.02% or more.
[0074] On the other hand, if the V content exceeds 0.50%, the magnetic properties may deteriorate. Therefore, the V content is set to 0.50% or less. The V content is preferably 0.30% or less, and more preferably 0.20% or less.
[0075] B: 0~0.0200% Boron (B) has the function of stabilizing secondary recrystallization. To achieve the above effect, the B content can be set to more than 0.0000%, or more than 0.0005%. On the other hand, if the B content exceeds 0.0200%, secondary recrystallization may become unstable. Therefore, the B content only needs to be 0.0200% or less. The B content is preferably 0.0100% or less, and more preferably 0.0050% or less.
[0076] Bi: 0~0.0200% Bismuth (Bi) has the effect of improving magnetic properties. Therefore, Bi can be included in the product. To obtain the above-mentioned effect, the Bi content can be set to more than 0.0000%, or more than 0.0005%. On the other hand, if the Bi content exceeds 0.0200%, the sheet permeability during cold rolling may deteriorate. In addition, if the purification during the annealing of the finished product is insufficient, resulting in excessive Bi residue, it may adversely affect the magnetic properties. Therefore, the Bi content only needs to be 0.0200% or less. The Bi content is preferably 0.0150% or less, and more preferably 0.0100% or less.
[0077] Te: 0~0.0200% Te (tellurium) has the function of stabilizing secondary recrystallization. To achieve the above effect, the Te content can be set to more than 0.0000%, or more than 0.0005%. If the Te content exceeds 0.0200%, fracture may occur during hot rolling or cold rolling. Therefore, the Te content only needs to be 0.0200% or less. The Te content is preferably 0.0150% or less, and more preferably 0.0100% or less.
[0078] Remaining components: Fe and impurities The chemical composition of the slab used in the manufacturing method of the directional electromagnetic steel sheet of this embodiment contains the elements described above, and the remainder may also be Fe and impurities. Here, impurities refer to elements that are introduced into the raw material, such as ore, waste, or from the manufacturing environment, during the industrial manufacturing of the base steel sheet. These are elements that are allowed to be present in a quantity that does not adversely affect the function of the directional electromagnetic steel sheet of this embodiment.
[0079] (Hot-rolled plate annealing process) The hot-rolled sheet annealing process is a process of annealing hot-rolled steel sheets manufactured through the hot rolling process. By performing this annealing treatment, recrystallization occurs in the steel sheet structure, resulting in good magnetic properties.
[0080] In the hot-rolled sheet annealing process of this embodiment, the hot-rolled steel sheet manufactured by the hot-rolling process is annealed according to a known method. There are no particular limitations on the means of heating the hot-rolled steel sheet during annealing; known heating methods can be used. Furthermore, there are no particular limitations on the annealing conditions, but for example, the hot-rolled steel sheet can be annealed in a temperature range of 900–1200°C for 10 seconds to 5 minutes.
[0081] (Cold rolling process) In the cold rolling process, hot-rolled steel sheets after the annealing process are subjected to cold rolling in multiple passes to obtain cold-rolled steel sheets. Cold rolling can be a single cold rolling process, or it can be interrupted before the final pass of the cold rolling process to perform at least one or two intermediate annealing processes, or multiple cold rolling processes with intermediate annealing interspersed.
[0082] When performing intermediate annealing, it is preferable to hold at a temperature of 1000–1200°C for 5–180 seconds. The annealing atmosphere is not particularly limited. Considering manufacturing costs, the number of intermediate annealing cycles is preferably no more than 3.
[0083] The total reduction rate in the cold rolling process is set to 89% or more. If the total reduction rate is less than 89%, a preferred primary recrystallization texture cannot be obtained. Specifically, if the total reduction rate is less than 89%, the sharpness of the Gaussian orientation that forms the nuclei for secondary recrystallization cannot be sufficiently obtained, and therefore, good magnetic properties may not be achieved. The total reduction rate in the cold rolling process is preferably 90% or more, more preferably 91% or more, and even more preferably 92% or more.
[0084] Before the cold rolling process, the surface of the hot-rolled steel sheet can also be pickled under known conditions.
[0085] (Decarburization annealing process) In the decarburization annealing process, cold-rolled steel sheets are decarburized and annealed to produce decarburized annealed steel sheets. In decarburization annealing, the cold-rolled steel sheet is recrystallized once, and carbon that adversely affects magnetic properties is removed from the steel sheet. However, in the manufacturing method of directional electromagnetic steel sheets in this embodiment, the steel sheet is locally heated before being heated to the annealing temperature.
[0086] That is, the decarburization annealing process in this embodiment includes the following steps: (IV-1) A local heating process in which the surface of the above-mentioned cold-rolled steel sheet is partially heated by laser beam irradiation in an atmospheric atmosphere at intervals of 5 to 30 mm in a direction at an angle of 30 to 150° relative to the rolling direction. (IV-2) The process of raising the temperature of a cold-rolled steel sheet after localized heating to the decarburization annealing temperature range of 750–950°C in a non-oxidizing atmosphere at an average heating rate of 80°C / second or higher; and (IV-3) The above-mentioned cold-rolled steel sheet after the heating process is subjected to an oxygen potential P that satisfies the following formula (1). O The homogenization process is carried out for decarburization annealing.
[0087] [Local heating process] During the local heating process, the surface of the cold-rolled steel sheet is partially heated in an atmospheric atmosphere by laser beam irradiation at intervals of 5 to 30 mm in a direction at an angle of 30 to 150° relative to the rolling direction.
[0088] More specifically, in the localized heating process, a laser beam-based heating element extends in a direction of 30–150° relative to the rolling direction (±60° relative to the direction perpendicular to the rolling direction), and is arranged in multiple linear configurations at intervals of 5–30 mm in the rolling direction, heating the surface of the cold-rolled steel sheet in an atmospheric atmosphere. The locally heated cold-rolled steel sheet exhibits… Figure 1 Such a linear heating element.
[0089] In the manufacturing method of the directional electromagnetic steel sheet of this embodiment, Gaussian-oriented grains are enriched in the heated portion by locally heating the steel sheet. The arrangement of the region enriched with Gaussian-oriented grains can also be set as a line extending in the direction intersecting the rolling direction, and it is preferable to repeat this process at predetermined intervals in the rolling direction.
[0090] The extension direction of the linear heating section is less than 30° or more than 150° relative to the rolling direction.
[0091] When the direction is nearly parallel to the rolling direction (above 30° or below 150°), although the reason is unknown, it is possible that the deviation angle of the Gaussian orientation grains after secondary recrystallization increases and the magnetic flux density decreases.
[0092] When the spacing between the linear heating sections exceeds 30 mm, it may be impossible to obtain sufficient Gaussian-oriented grains that can serve as nuclei for secondary recrystallization, resulting in a decrease in magnetic flux density. On the other hand, if the spacing between the linear heating sections is set to less than 5 mm, there will be too many Gaussian-oriented grains, reducing the number of corresponding oriented grains that promote the growth of Gaussian-oriented grains and decreasing the aggregation degree toward Gaussian orientation.
[0093] The spacing between the linear heating sections can also be approximately equal, but as long as it falls within the aforementioned range, it can be controlled by making the spacing between adjacent linear heating sections different. For example, in the annealing process of a finished product annealed in a roll form, the inner periphery with small curvature can be enriched by narrowing the spacing between the heating sections, which will become the nuclei for secondary recrystallization, thereby achieving the reduction of the diameter of the secondary recrystallized grains.
[0094] The width of the linear heating section is preferably 0.2 to 1.0 mm. If it is less than 0.2 mm, the heating section is small, and the enrichment effect of Gaussian-oriented grains is reduced. On the other hand, if it exceeds 1.0 mm, it has the enrichment effect of Gaussian-oriented grains, but the corresponding oriented grains are reduced, so the deviation angle from the Gaussian orientation becomes larger after secondary recrystallization.
[0095] The length of the linear heating section is not limited, but it is preferred to be formed over the entire width of the steel plate or over the entire width except for the edge.
[0096] In addition, regarding local heating (the formation of a linear heating section), heating can be performed locally, and heating can be achieved by irradiation with a laser beam, which minimizes the impact on the surrounding environment.
[0097] When heating is achieved by laser beam irradiation, the average intensity of the laser beam is set to P (W), the focusing diameter of the focused spot in the rolling direction is set to Dl (mm), the focusing diameter of the focused spot in the width direction is set to Dc (mm), the irradiation time is set to t (seconds), and the instantaneous input energy, expressed as 4 / π×P / (Dl×Dc)×t, is set to Up (J / mm²). 2 When ), the laser beam is irradiated under the condition that the following equation (2) is satisfied.
[0098] The focusing diameter Dc is Figure 2 The diameter of the focused beam spot in the rolling direction is shown. The focused beam diameter Dc is... Figure 2The diameter of the focused laser spot shown is in the width direction (orthogonal to the rolling direction). The laser beam irradiates the steel plate of the through sheet for a specified time t. When irradiating the entire width direction of the steel plate, multiple irradiation spots can also be arranged in series along the width direction.
[0099] 0.5≤Up≤5 (2).
[0100] By setting the condition to satisfy equation (2), the length of the rolling direction of the secondary recrystallized grains can be reduced, and the difference in the degree of orientation aggregation towards the Gaussian orientation becomes smaller. Without satisfying equation (2), the effect is not sufficient.
[0101] It should be noted that the purpose of irradiating the laser beam in this embodiment is not magnetic domain control, but rather microstructure control as described above. That is, during the heating process of the decarburization annealing process in this embodiment, only the surface layer of the steel plate is heated locally, and grooves on the surface of the steel plate are not formed as in general magnetic domain control.
[0102] [Heating process] During the heating process, the cold-rolled steel sheet after the local heating process is heated in a non-oxidizing atmosphere at an average heating rate of more than 80°C / second from a temperature range below 450°C to a temperature range of 750-950°C, which is the decarburization annealing temperature.
[0103] The aforementioned heating promotes the formation of Gaussian-oriented grain nuclei. When the average heating rate within the aforementioned temperature range is less than 80°C / second, nuclei formation becomes insufficient, and the grain size of the secondary recrystallized grains increases. Furthermore, when performing localized heating to reduce the secondary recrystallized grain size in the rolling direction, sufficient secondary recrystallization nuclei are required to completely cover the entire surface of the steel sheet with a Gaussian orientation exhibiting good magnetic properties. Therefore, an average heating rate of 160°C / second or higher is preferred, and more preferably 240°C / second or higher. There is no upper limit to the heating rate; it can be determined based on the equipment capacity. For example, it can be 2000°C / second or lower.
[0104] If the atmosphere during heating is not a non-oxidizing atmosphere, a dense SiO2 film will form on the surface of the steel plate, resulting in poor decarburization and poor film formation after annealing. In this embodiment, a non-oxidizing atmosphere refers to a nitrogen atmosphere or a nitrogen / hydrogen mixed atmosphere, with a dew point of -50°C to 0°C. From the viewpoint of suppressing SiO2 formation on the surface of the steel plate and thus ensuring good decarburization, the dew point is preferably below -5°C or below -10°C. From the viewpoint of ensuring good internal oxidation for ease of process control, the dew point can be, for example, above -40°C.
[0105] There is no limitation to the annealing process after heating to 750-950°C, but for example, the oxidation degree (PH2O / PH2) in the annealing atmosphere (furnace atmosphere) can be set to 0.15-1.0 and held in this temperature range for 10-600 seconds.
[0106] [Easing heating process] During the homogenization process, the above-mentioned cold-rolled steel sheet after the heating process is subjected to an oxygen potential P that satisfies the following formula (1). O Perform decarburization annealing.
[0107] P O ≤0.6-0.04Up (1).
[0108] It is believed that, as mentioned above, in the laser beam irradiation section, it is more difficult to form the SiO2 internal oxide layer during the homogenization process compared to the non-irradiation section. Therefore, in the subsequent finished product annealing process, the amount of primary film formed at the laser beam irradiation section is reduced, resulting in decreased film adhesion.
[0109] Therefore, in the homogenization process of this embodiment, the oxygen potential P during the homogenization process is controlled by combining the laser beam irradiation conditions, specifically by combining "Up". O The inhibition is relatively low, thereby promoting the formation of the internal oxide layer of SiO2 during the homogenization process. Specifically, the oxygen potential P satisfies equation (1) O To perform annealing.
[0110] By undergoing the decarburization annealing process described above, the Gaussian-oriented grains that will become the nuclei for secondary recrystallization are enriched only in the surface layer of the steel plate through localized rapid heating based on a laser beam. This promotes the secondary recrystallization of Gaussian-oriented grains with excellent magnetic properties and promotes the formation of an internal SiO2 oxide layer in the entire steel plate, including the laser beam irradiation area. Therefore, it becomes possible to achieve both excellent magnetic properties and film adhesion.
[0111] (Finished product annealing process) In the finished product annealing process, the decarburized annealed steel sheet obtained in the decarburization annealing process is coated with a specified annealing release agent on one or both sides before finished product annealing. Finished product annealing is generally carried out for a long time while the steel sheet is rolled into a coil. Therefore, before finished product annealing, in order to prevent sand from adhering to the inside and outside of the coil, an annealing release agent is applied to the decarburized annealed steel sheet and allowed to dry.
[0112] As the annealing release agent used for coating, an annealing release agent with MgO as the main component (e.g., containing more than 80% by weight) is used. By using an annealing release agent with MgO as the main component, a glass coating can be formed on the surface of the base steel sheet. Without MgO as the main component, a primary coating (glass coating) will not form. This is because the primary coating is a Mg₂SiO₄ or MgAl₂O₄ compound, and without MgO as the main component, the Mg required for the reaction is lacking.
[0113] The finished product can be annealed under the following conditions: in an atmosphere containing hydrogen and nitrogen, the temperature is raised to 1150-1250°C and annealed for 10-60 hours in this temperature range.
[0114] <3. Directional Electromagnetic Steel Sheet> Next, the directional electromagnetic steel sheet obtained by the above manufacturing method will be explained.
[0115] (3-1. Chemical composition of the base steel plate) First, the chemical composition of the base steel sheet for directional electromagnetic steel sheets will be explained. In the following explanation, unless otherwise specified, "%" will be used to represent "mass %" relative to the total mass of the base steel sheet.
[0116] C: 0.0005~0.010% Carbon (C) is an element that adversely affects the magnetic properties of directional electromagnetic steel sheets, so it is preferable to use as little as possible. In this embodiment, the C content is 0.010% or less. Setting the C content to 0% is difficult in industrial applications. Therefore, approximately 0.0005% is a practically acceptable lower limit for the C content.
[0117] Si: 2.50~4.00% Silicon (Si) is an extremely effective element for increasing the resistivity of steel, thereby reducing eddy current losses, which constitute part of iron losses. When the Si content is below 2.50%, the resistivity is low, and eddy current losses cannot be sufficiently reduced. Furthermore, during secondary recrystallization annealing, the steel undergoes a phase transformation, and secondary recrystallization is not fully achieved, resulting in insufficient magnetic flux density and low iron losses.
[0118] Therefore, the Si content is set to 2.50% or more. The Si content is preferably 2.70% or more, and more preferably 2.80% or more.
[0119] On the other hand, when the Si content exceeds 4.00%, the steel sheet becomes brittle, and the permeability during manufacturing processes deteriorates significantly. Therefore, the Si content is set to 4.00% or less. The Si content is preferably 3.90% or less, and more preferably 3.80% or less.
[0120] Mn: 0.01~0.30% Manganese (Mn) is an important element in the formation of MnS, which is one of the main inhibitors. When the Mn content is less than 0.01%, the absolute amount of MnS required for secondary recrystallization is insufficient. Therefore, the Mn content is set to 0.01% or more. The Mn content is preferably 0.03% or more, and more preferably 0.06% or more.
[0121] On the other hand, when the Mn content exceeds 0.30%, the steel undergoes a phase transformation during secondary recrystallization annealing, and secondary recrystallization is not sufficient, resulting in poor magnetic flux density and low iron loss. Therefore, the Mn content is set to 0.30% or less. The Mn content is preferably 0.28% or less, and more preferably 0.26% or less.
[0122] Selected from one or more of S and Se: 0 to 0.010% S and Se are elements that serve as raw materials for MnS and MnSe, which act as inhibitors, but they also negatively affect the magnetic properties of directional electromagnetic steel sheets. Therefore, their content in the base steel sheet is preferably as low as possible. In this embodiment, the total content of S and Se is 0.010% or less. The total content of S and Se can also be 0%. The total content of S and Se can also be 0.0005% or more.
[0123] sol.Al: 0~0.010% As described above, sol.Al is an element that serves as a raw material for AlN, which acts as an inhibitor, but it also negatively affects the magnetic properties of directional electromagnetic steel sheets. Therefore, its content in the base steel sheet is preferably as low as possible. In this embodiment, the sol.Al content is 0.010% or less. The sol.Al content may also be 0%. The sol.Al content may also be 0.0005% or more.
[0124] N: 0.0001~0.0100% As mentioned above, nitrogen (N) is an element that serves as a raw material for AlN, which acts as an inhibitor, but it also negatively affects the magnetic properties of directional electromagnetic steel sheets. Therefore, its content in the base steel sheet is preferably as low as possible. In this embodiment, the N content is set to 0.0100% or less. Setting the N content to 0% is difficult in industry, so approximately 0.0001% is a practically acceptable lower limit for the N content.
[0125] Ni: 0~0.50% Ni (Ni) is an effective element for increasing electrical resistance and thus reducing iron loss. Furthermore, Ni is effective in controlling the microstructure of hot-rolled steel sheets and improving magnetic properties. Therefore, Ni may be included. To achieve the above effects, the Ni content is preferably set to 0.01% or more. More preferably, the Ni content is 0.02% or more.
[0126] On the other hand, if the Ni content exceeds 0.50%, secondary recrystallization may become unstable. Therefore, the Ni content is set to 0.50% or less. Preferably, the Ni content is 0.30% or less.
[0127] Cu: 0~0.50% Cu (copper) is an element that contributes to increasing the Gaussian orientation occupancy in the secondary recrystallization structure and improves the adhesion of the glass film. Therefore, Cu may be included. To obtain the above-mentioned effects, it is preferable to set the Cu content to 0.01% or more. More preferably, the Cu content is 0.02% or more, and even more preferably 0.03% or more.
[0128] On the other hand, when the Cu content exceeds 0.50%, the steel sheet becomes brittle during hot rolling. Therefore, the Cu content of the slab is set to 0.50% or less. The Cu content is preferably 0.30% or less, and more preferably 0.10% or less.
[0129] Sb: 0~0.30% Antimony (Sb) is an element that improves magnetic properties. Therefore, it may be present in a container. When Sb is present, it is preferable to set the content to 0.01% or more to maximize the improvement in magnetic properties. More preferably, the Sb content is 0.02% or more.
[0130] On the other hand, if the Sb content exceeds 0.30%, the adhesion of the glass coating deteriorates. Therefore, the Sb content is set to 0.30% or less. Preferably, the Sb content is 0.20% or less.
[0131] Sn: 0~0.30% Sn (tin) is an element that improves magnetic properties. Therefore, Sn can be included. When Sn is included, it is preferable to set the Sn content to 0.01% or more in order to fully exert the effect of improving magnetic properties. If both magnetic properties and film adhesion are considered, the Sn content is preferably 0.02% or more, and more preferably 0.03% or more.
[0132] On the other hand, if the Sn content exceeds 0.30%, the glass coating deteriorates significantly, and sufficient tension is not obtained for magnetic domain refinement, thus deteriorating the iron loss characteristics. Therefore, the Sn content is set to 0.30% or less. The Sn content is preferably 0.20% or less, and more preferably 0.15% or less.
[0133] Cr: 0~0.50% Cr (chromium) is an element that, like Sn and Cu described later, contributes to increasing the Gaussian orientation occupancy in the secondary recrystallization structure, thereby improving magnetic properties and enhancing the adhesion of the glass film. Therefore, Cr may also be included. To obtain the above effects, it is preferable to set the Cr content to 0.01% or more, more preferably 0.02% or more, and even more preferably 0.03% or more.
[0134] On the other hand, when the Cr content exceeds 0.50%, Cr oxide is formed, which reduces the magnetic properties. Therefore, the Cr content is set to 0.50% or less. The Cr content is preferably 0.30% or less, and more preferably 0.10% or less.
[0135] P: 0–0.05% Phosphorus (P) is an element that reduces workability during rolling. By setting the P content to 0.05% or less, excessive reduction in rolling workability can be prevented, and breakage during manufacturing can be suppressed. From this point of view, the P content is set to 0.05% or less. The P content is preferably 0.04% or less.
[0136] There is no lower limit to the phosphorus (P) content; it can be as low as 0%. However, P is also an element that can improve texture and magnetic properties. To achieve this effect, the P content can be set to 0.005% or higher, or 0.01% or higher.
[0137] Mo: 0–0.05% Mo (molybdenum) is an element that improves magnetic properties. Therefore, it may be present in the composition of a metal. When Mo is present, to maximize the improvement in magnetic properties, it is preferable to set the Mo content to 0.01% or more. More preferably, the Mo content is 0.02% or more, and even more preferably 0.03% or more.
[0138] On the other hand, if the Mo content exceeds 0.05%, cold rollability may deteriorate, leading to breakage. Therefore, the Mo content is set to 0.05% or less. Preferably, the Mo content is 0.04% or less.
[0139] Ta: 0~0.05% Ta (tantalum) has the function of stabilizing secondary recrystallization. To obtain the above effect, the Ta content can be set to more than 0.0000% or more than 0.0005%. On the other hand, if the Ta content exceeds 0.05%, secondary recrystallization may become unstable. Therefore, the Ta content only needs to be 0.05% or less. The Ta content is preferably 0.04% or less.
[0140] Nb: 0~0.010% Niobium (Nb) has the function of stabilizing secondary recrystallization. To achieve the above effect, the Nb content can be set to more than 0.0000% or more than 0.0005%. On the other hand, if the Nb content exceeds 0.010%, secondary recrystallization may become unstable. Therefore, the Nb content only needs to be 0.010% or less. The Nb content is preferably 0.0050% or less.
[0141] V: 0~0.50% Vanadium (V) is an effective element that combines with nitrogen (N) and carbon (C) to function as an inhibitor. Therefore, it may also contain V. To achieve the above-mentioned effects, the V content is preferably 0.01% or more, more preferably 0.02% or more.
[0142] On the other hand, if the V content exceeds 0.50%, the magnetic properties may deteriorate. Therefore, the V content is set to 0.50% or less. The V content is preferably 0.30% or less, and more preferably 0.20% or less.
[0143] B: 0~0.0200% Boron (B) has the function of stabilizing secondary recrystallization. To achieve the above effect, the B content can be set to more than 0.0000%, or more than 0.0005%. On the other hand, if the B content exceeds 0.0200%, secondary recrystallization may become unstable. Therefore, the B content only needs to be 0.0200% or less. The B content is preferably 0.0100% or less, and more preferably 0.0050% or less.
[0144] Bi: 0~0.0200% Bismuth (Bi) has the effect of improving magnetic properties. Therefore, Bi can be included in the product. To obtain the above-mentioned effect, the Bi content can be set to more than 0.0000%, or more than 0.0005%. On the other hand, if the Bi content exceeds 0.0200%, the sheet permeability during cold rolling may deteriorate. In addition, if the purification during the annealing of the finished product is insufficient, resulting in excessive Bi residue, it may adversely affect the magnetic properties. Therefore, the Bi content only needs to be 0.0200% or less. The Bi content is preferably 0.0150% or less, and more preferably 0.0100% or less.
[0145] Te: 0~0.0200% Te (tellurium) has the function of stabilizing secondary recrystallization. To achieve the above effect, the Te content can be set to more than 0.0000%, or more than 0.0005%. If the Te content exceeds 0.0200%, fracture may occur during hot rolling or cold rolling. Therefore, the Te content only needs to be 0.0200% or less. The Te content is preferably 0.0150% or less, and more preferably 0.0100% or less.
[0146] Remaining components: Fe and impurities The chemical composition of the base steel plate of the directional electromagnetic steel plate in this embodiment contains the elements described above, and the remainder may also be Fe and impurities. Here, impurities refer to elements that may be introduced during the industrial manufacturing of the base steel plate from the ore used as raw material, waste, or from the manufacturing environment, etc., and are elements that are allowed to be present in a quantity that does not adversely affect the function of the directional electromagnetic steel plate of this embodiment.
[0147] It should be noted that the chemical composition of the aforementioned slabs and base steel plates can be determined using general analytical methods. For example, the steel composition can be determined using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). Furthermore, C and S can be determined using the combustion-infrared absorption method, N can be determined using the inert gas melting-thermal conductivity method, and O can be determined using the inert gas melting-non-dispersive infrared absorption method.
[0148] (3-2. Composition and characteristics of directional electromagnetic steel sheets) Next, the structure and characteristics of the directional electromagnetic steel plate of this embodiment will be explained.
[0149] <Crystal Orientation> As described above, in the decarburizing annealing process of the grain-oriented electrical steel sheet of the present embodiment, fine control of the irradiation conditions for local rapid heating treatment based on a laser beam and control of the oxygen potential in the decarburizing annealing process according to the laser beam irradiation conditions are performed together. As a result, in the obtained grain-oriented electrical steel sheet, secondary recrystallization of {211}<011> oriented grains can be sufficiently suppressed, and promotion of secondary recrystallization of Goss oriented grains with excellent magnetic properties and reduction of non-uniformity of magnetic properties can be achieved.
[0150] Specifically, when measurement points of crystal orientation based on X-ray diffraction are arranged at intervals of 6 mm in the rolling direction and in the direction orthogonal to the rolling direction on the surface of the base steel sheet, the ratio of the measurement points with an orientation difference from {211}<011> of 15° or less to all the measurement points is 5% or less. Thereby, the magnetic properties of the grain-oriented electrical steel sheet can be further improved.
[0151] The method for measuring crystal orientation is as described below.
[0152] A sample of 60 mm × 300 mm × sheet thickness is collected from the grain-oriented electrical steel sheet, and crystal orientation measurement is performed using the Laue method. In the Laue measurement, orientation data of 171 measurement points are obtained at intervals of 6 mm in the rolling direction and in the direction orthogonal to the rolling direction at the center of the sheet. The number of crystal orientation data with a deviation angle from {211}<011> of 15° or less is analyzed from the orientation data of all the measurement points, and the ratio R occupied in all the measurement points (171 points) is calculated.
[0153] <EPMA analysis> In addition, as described above, it is considered that there is a correlation between the film adhesion at the laser beam irradiation portion and the formation amount of the primary film, i.e., forsterite. Therefore, in the grain-oriented electrical steel sheet of the present embodiment, the formation amount is specified by the analysis data of an electron probe microanalyzer (EPMA).
[0154] Specifically, in the grain-oriented electrical steel sheet of the present embodiment, in the oxygen intensity distribution on the surface of the primary film obtained by line analysis along the rolling direction using EPMA, oxygen intensity reduction regions exist periodically, and the minimum value Io of the oxygen intensity in the oxygen intensity reduction regions min and the maximum value Io of the oxygen intensity in the regions other than the oxygen intensity reduction regions max The ratio Io min / Io max is 0.85 to 0.96.
[0155] Figure 3 is a schematic diagram of the oxygen intensity distribution measured by line analysis of the primary film surface using EPMA. As Figure 3As shown, in the distribution of oxygen intensity along the rolling direction of the primary coating surface measured by EPMA, a region of reduced oxygen intensity appears at the laser beam irradiation area. This means that the amount of primary coating, i.e., forsterite, formed is reduced by the laser beam irradiation area. In this embodiment, since the irradiation interval L of the laser beam irradiation is 5 to 30 mm, the oxygen intensity reduction region also appears at intervals L of 5 to 30 mm.
[0156] In the directional electromagnetic steel sheet of this embodiment, the decrease in oxygen intensity in the oxygen intensity reduction region is suppressed. Specifically, the minimum value Io of the oxygen intensity in the oxygen intensity reduction region is... min Oxygen intensity Io in other parts max The ratio of Io min / Io max Set it to 0.85 or higher. min / Io max When the value is below 0.85, the adhesion of the coating at the laser beam irradiation site becomes poor, therefore Io min / Io max Set to 0.85 or higher. Preferably 0.87 or higher. Regarding Io... min / Io max There is no specific upper limit to the oxygen intensity ratio; theoretically, it can be 1. However, in practice, when local heating is achieved through laser beam irradiation, approximately 0.96 becomes the upper limit. To obtain such an oxygen intensity ratio, for example, in the homogenization process of the aforementioned decarburization annealing process, the oxygen potential P is... O Set it to 0.6-0.04Up or below.
[0157] The specific methods for EPMA analysis are described below.
[0158] First, a 50mm square test piece is taken from the directional electromagnetic steel sheet with a secondary coating. Next, an alkaline solution is used to remove the secondary coating. For example, the secondary coating can be removed by immersing the directional electromagnetic steel sheet with the secondary coating in an aqueous solution of sodium hydroxide (NaOH: 30–50 wt% + H₂O: 50–70 wt%) at 80–90°C for 5–10 minutes, followed by washing with water and drying.
[0159] Next, the surface of the primary coating after the secondary coating was removed was analyzed using an EPMA (JEOL, JXA-8230) to obtain the oxygen intensity distribution. The EPMA analysis conditions were set as follows: accelerating voltage 15.0 kV, irradiation current 100 nA, and beam shape 10 μm × 300 μm strip. Measurements were performed 15 times at 3 mm intervals (totaling 45 mm) in 10 μm increments along the rolling direction, and line analysis was conducted in the rolling direction. The obtained oxygen intensity measurement data along the rolling direction were used to calculate a moving average of 10 intervals, starting from the maximum intensity Io. max and minimum intensity Io min Calculate its ratio Io min / Io max .
[0160] It should be noted that, in order to observe the region of reduced oxygen intensity, the distance for line analysis should be set to be longer than the width of the laser irradiation. For example, if the laser irradiation width is 30 mm, the distance for line analysis should be set to be greater than 30 mm.
[0161] <Thickness> From the viewpoint of reducing iron loss, the thickness of the directional electromagnetic steel sheet in this embodiment is preferably 0.15 to 0.35 mm. In particular, the thickness of the directional electromagnetic steel sheet is more preferably 0.18 mm or less.
[0162] Furthermore, from the viewpoint of reducing iron loss, the thickness of the base steel plate of the directional electromagnetic steel plate in this embodiment is preferably 0.14 to 0.22 mm. In particular, the thickness of the base steel plate is more preferably 0.17 mm or less.
[0163] Example The following describes embodiments of the present invention. However, the conditions described in these embodiments are merely examples used to confirm the feasibility and effectiveness of the present invention, and the present invention is not limited to these single examples. Various conditions may be used as long as they do not depart from the spirit and purpose of the present invention.
[0164] Prepare a slab with the chemical composition shown in Tables 1A-1D, the remainder being Fe and impurities. Heat the slab to 1340°C in a furnace. Perform a hot rolling process on the heated slab to produce a hot-rolled steel sheet with the thicknesses shown in Tables 3A-3D. Next, perform a hot-rolled annealing process on the hot-rolled steel sheet at a holding time of 10-300 seconds at a hot-rolled annealing temperature of 900-1200°C. After hot-rolled annealing, perform a cold rolling process to produce a cold-rolled steel sheet with the thicknesses shown in Tables 3A-3B.
[0165] Next, for the obtained cold-rolled steel sheet, the heating section is extended at an angle (deg.) to the rolling direction as shown in Tables 3A to 3D, and is subjected to localized heating based on a laser beam in an atmospheric atmosphere, arranged as multiple straight lines with a spacing (interval L) (mm) as shown in Tables 3A to 3B in the rolling direction. The irradiation conditions are as shown in Tables 3A to 3B.
[0166] Next, regardless of whether heating is based on the laser beam, the temperature is increased in a nitrogen / hydrogen mixed gas (non-oxidizing atmosphere) with a dew point of -20°C, in a manner that follows the average heating rate from the temperature range below 400°C to the temperature range of 750 to 900°C as shown in Tables 3C to 3D.
[0167] After heating, the oxygen potential P in the annealing atmosphere is... O The steel sheet was decarburized and annealed by setting the temperature as shown in Tables 3C to 3D and performing homogenization at 850°C for 120 seconds to obtain the decarburized annealed steel sheet.
[0168] An annealing separating agent (water slurry) with MgO as the main component is coated on the surface of the decarburized annealed steel sheet. Then, the decarburized annealed steel sheet coated with the annealing separating agent is rolled into a coil. The coil is then subjected to finished annealing to produce a finished annealed steel sheet. The finished annealing temperature is set to 1100℃~1200℃, and the holding time at the finished annealing temperature is set to 5~30 hours.
[0169] For steel plates after the finished annealing process, a secondary coating formation process (insulating film formation process) is implemented.
[0170] Specifically, a secondary coating forming agent (insulating coating agent) mainly composed of colloidal silica and phosphate is applied to the surface (glass film) of each finished annealed steel sheet. The finished annealed steel sheet coated with the secondary coating forming agent is then baked, thereby forming a secondary coating as a tension insulating film on the primary coating. Through the above manufacturing process, directional electromagnetic steel sheets with various test numbers are manufactured.
[0171] The chemical composition of the base steel plate was determined by the following compositional analysis method.
[0172] First, the primary and secondary coatings are removed from the base steel sheet using the following method. Specifically, the directional electromagnetic steel sheet with the secondary coating is immersed in a sodium hydroxide aqueous solution of NaOH (30-50% by mass) + H₂O (50-70% by mass) at 80-90°C for 5-10 minutes, followed by washing and drying. This process removes the secondary coating from the directional electromagnetic steel sheet.
[0173] Next, the directional electromagnetic steel sheet with the secondary coating removed and the primary coating residue remaining is immersed in high-temperature hydrochloric acid for further removal. Specifically, the directional electromagnetic steel sheet with the primary coating residue is immersed in 30-40% hydrochloric acid at 80-90°C for 1-5 minutes, followed by washing with water and drying. Through the above processes, a base steel sheet with the secondary coating and the primary coating removed is obtained.
[0174] The chemical composition of the base steel sheet for each test number of the directional electromagnetic steel sheet was determined using the following method.
[0175] First, using the method described above, the primary and secondary coatings of the directional electromagnetic steel sheet are removed, and the base steel sheet is extracted. Using the base steel sheet, its chemical composition is analyzed based on the following measurement methods.
[0176] The chemical composition of the obtained steel sheet was determined according to the method of JIS G0321:2017. Specifically, firstly, chips were collected from the obtained base steel sheet, and the collected chips were dissolved in acid to obtain a solution. Next, elemental analysis of the chemical composition was performed on the solution using ICP-AES (Inductively Coupled Plasma Atomic Emission Spectrometry). The C and S contents were determined using the well-known high-frequency combustion method (combustion-infrared absorption method). The N content was determined using the well-known inert gas melting-thermal conductivity method. Specifically, the composition analysis device (trade name: ICPS-8000) manufactured by Shimadzu Corporation was used for the determination.
[0177] The analysis results show that the chemical composition of the base steel plate contains the components listed in Tables 2A to 2D, with the remainder being Fe and impurities. It should be noted that "0.00", "0.000", and "0.0000" in Tables 1A to 1D and Tables 2A to 2D indicate that the content of the corresponding element is below the detection limit.
[0178] <Evaluation> The following measurements and evaluations were performed on the obtained electromagnetic steel plates of various orientations.
[0179] [Magnetic Property Measurement] Test pieces were collected from the grain-oriented electrical steel sheet coils of each test number. Regarding the collection positions, the position about 10 m from the outer peripheral part of the coil after the completion of finish annealing was defined as the outer peripheral part, and the position at 50% of the total length of the coil was defined as the central part, and two positions were set. The size of the test piece was set to 60 mm × 300 mm × sheet thickness. The test piece included the central part of the sheet width of the grain-oriented electrical steel sheet. According to JIS C2556:2015, through the single sheet magnetic property test (SST test), a magnetic field of 800 A / m was applied to the test piece, and the magnetic flux density B8 (T) was obtained. The obtained magnetic flux density B8 is shown in "Magnetic Flux Density B8 (T)" in Table 1-3. When the magnetic flux density B8 is 1.902 T or more, it is evaluated that the magnetic properties are excellent and set as qualified.
[0180] [Crystal Orientation Measurement] For the 60 mm × 300 mm × sheet thickness sample after magnetic property measurement, the crystal orientation measurement was carried out using the Laue method. In the Laue measurement, orientation data of 171 measurement points were obtained at intervals of 6 mm at the center of the sheet. The number of crystal orientation data with a deviation angle of 15° or less from {211}<011> was analyzed from the orientation data of all the measurement points, and the ratio R occupied in all the measurement points (171 points) was calculated. Here, in the above magnetic property measurement, when the magnetic flux density B8 was less than 1.700 T, it was regarded as poor secondary recrystallization, and the crystal orientation measurement was not carried out.
[0181] [Film Adhesion Evaluation] Test pieces were collected from the grain-oriented electrical steel sheets of each test number. Regarding the collection positions, the position about 10 m from the outer peripheral part of the coil after the completion of finish annealing was defined as the outer peripheral part, and the position at 50% of the total length of the coil was defined as the central part, and two positions were set. The size of the test piece was set to a length of 15 mm in the rolling right-angle direction and a length of 60 mm in the rolling direction. It was wound around round bars with various diameters, and the film adhesion was evaluated by the smallest diameter at which the film was not peeled off visually (hereinafter referred to as the bending peel-off diameter). The smaller the bending peel-off diameter, the better the film adhesion. When the bending peel-off diameter was 40 mm or more, the concern about film peeling during core manufacturing increased, so it was set as unqualified.
[0182] [EPMA Analysis (Primary Film Evaluation)] 50mm square test pieces were collected from directional electromagnetic steel plates of various test numbers. The secondary coating was removed using the method described above. The oxygen intensity distribution was obtained by line analysis of the surface of the primary coating after the secondary coating was removed using an EPMA (JEOL, JXA-8230). The EPMA analysis conditions were set as follows: accelerating voltage 15.0kV, irradiation current 100nA, and beam shape 10μm×300μm strip. Measurements were performed 15 times at 3mm intervals in 10μm increments along the rolling direction, and line analysis was conducted along the rolling direction. The obtained oxygen intensity measurement data along the rolling direction were used to calculate a moving average of 10 intervals, starting from the maximum intensity Io. max and minimum intensity Io min Calculate its ratio Io min / Io max .
[0183] <Evaluation Results> The thickness and composition of the directional electromagnetic steel sheet are as shown in Tables 2A to 2D.
[0184] The results of the magnetic property measurement, crystal orientation measurement, and coating adhesion evaluation of the directional electromagnetic steel sheet are shown in Tables 3E to 3F. When the magnetic flux density B8 is below 1.700T, no crystal orientation measurement or coating adhesion evaluation was performed, therefore this field is left blank.
[0185] Any of the conditions in tests 1 through 30 is appropriate. Therefore, the magnetic flux density B8 in the central and outer periphery of the roll material is above 1.902 T, {211} <011> The presence rate of poorly magnetic grains is less than 5%. Additionally, Io min / Io max With a value of 0.85 to 0.96, the bending peel diameter is less than 30 mm, indicating good film adhesion.
[0186] The rolling reduction rates for tests 31, 32, 51, and 52 are unsuitable. Although tests 31 and 51, with rolling reduction rates below 89%, {211} <011> The ratio is low, but the magnetic flux density B8 is low. This is believed to be due to the low reduction rate, resulting in a large deviation angle despite the high Gaussian orientation. On the other hand, test numbers 32 and 52 {211} have rolling reduction rates of over 94%. <011> The ratio is high, and the magnetic flux density B8 is low. This is believed to be due to: a high compression ratio, therefore {211} <011> It develops during cold rolling, which makes it easy for secondary recrystallization to occur.
[0187] Experiments 33, 34, 53, and 54 did not employ laser beam-based heating. The subsequent decarburization annealing process in experiments 33 and 53 also exhibited a low heating rate and significantly low magnetic flux density B8. The subsequent decarburization annealing process in experiments 34 and 54 had a high heating rate, but {211} <011> The ratio is high, therefore the magnetic flux density B8 is poor. It is believed that because laser-beam-based heating was not implemented, a sufficiently Gaussian orientation could not be obtained, {211} <011> Secondary recrystallization was performed.
[0188] Although laser beam-based heating was implemented in experiments 35, 36, 55, and 56, Up was not suitable. For experiments 35 and 55, where Up is below 0, laser beam-based heating was insufficient, therefore {211} <011> More, magnetic flux density B8 is low. Regarding test numbers 36 and 56 with Up values above 6, heating based on the laser beam becomes excessive, although {211} <011> The amount of magnetic flux is small, but the magnetic flux density is low. This is believed to be due to the fact that excessive heating causes the precipitates in the laser beam-irradiated section to coarsen, resulting in a loss of orientation selectivity during the secondary recrystallization of the Gaussian-oriented grains from the laser beam-irradiated section.
[0189] Although laser beam-based heating was implemented in experiments 37, 38, 57, and 58, the irradiation interval was unsuitable. Therefore, the magnetic flux density B8 was low. (Compared to {211}) <011> The presence rate of crystal orientations with a deviation angle within 15° is also above 5%. This is believed to be due to the insufficient enrichment effect of Gaussian orientation grains brought about by the laser beam.
[0190] Although laser beam-based heating was implemented in experiments 39, 40, 59, and 60, the angle of the irradiated area was unsuitable. {211} <011> Although few, the magnetic flux density B8 is low.
[0191] The reason is unclear, but it is believed that when the slope of the irradiated section is unsuitable, Gaussian-oriented grains with large deviations frequently undergo secondary recrystallization, although {211} <011> Secondary recrystallization is suppressed, but the orientation selectivity of Gaussian oriented grains is lost.
[0192] The heating rates in the ACL heating processes of experiments 41, 42, 61, and 62 were unsuitable. When the heating rate was below 80℃ / s, even with the application of a laser beam, the enrichment effect of Gaussian-oriented grains was insufficient; therefore, {211} <011> The magnetic flux density B8 is low when the heating rate exceeds 2000℃ / s. This is due to the reduced selective growth of Gaussian-oriented grains caused by the decrease in the number of corresponding oriented grains.
[0193] Experiments 43–50 and 63–70 exhibited good magnetic properties but deteriorated film adhesion due to unsuitable oxygen potential (Po) during the ACL homogenization process. When Po was below 0.3, Io… min / Io max The value is above 0.97. This is believed to be due to insufficient oxidation during the decarburization annealing process, resulting in inadequate primary film formation during finished product annealing and thus deterioration of film adhesion. When Po exceeds 0.6-0.04 Up, Io... min / Io max When the value drops below 0.85, the adhesion of the film near the laser beam irradiation area becomes poor.
[0194] [Table 1A] [Table 1B] [Table 1C] [Table 1D] [Table 2A] [Table 2B] [Table 2C] [Table 2D] [Table 3A] [Table 3B] [Table 3C] [Table 3D] [Table 3E] [Table 3F] Industrial availability According to the above-described scheme of the present invention, a directional electromagnetic steel sheet with excellent magnetic properties and film adhesion can be obtained. Therefore, the obtained directional electromagnetic steel sheet can be suitable for use as a core material of transformers, thus exhibiting high industrial applicability.
Claims
1. A directional electromagnetic steel plate, characterized in that, It comprises a base steel plate, a primary coating formed on the base steel plate, and a secondary coating formed on the primary coating. The chemical composition of the base steel plate, expressed as a percentage by mass, contains: Si: 2.50~4.00% Mn: 0.01~0.30%, N:0.0001~0.0100%、 C:0.0005~0.010%、 sol.Al: 0~0.010%, Selected from one or more of S and Se: totaling 0 to 0.010%. Ti: 0.001~0.010%, Ni: 0~0.50%, Cu: 0~0.50%, Sb: 0~0.30%, Sn: 0~0.30% Cr:0~0.50%、 P:0~0.05%、 Mo: 0–0.05%, Ta: 0~0.05%, Nb: 0~0.010%, V:0~0.50%、 B:0~0.010%、 Bi: 0~0.0100%, and Te: 0~0.0100%, The remaining portion contains Fe and impurities. The magnetic flux density B8 is above 1.902T. When X-ray diffraction-based crystal orientation measurement points are arranged at 6mm intervals on the surface of the base steel plate in both the rolling direction and in directions orthogonal to the rolling direction, with {211} <011> The proportion of measurement points with an orientation difference within 15° relative to all measurement points is less than 5%. In the oxygen intensity distribution on the surface of the primary coating obtained by line analysis along the rolling direction using an electron beam microscope, there are periodic regions where the oxygen intensity decreases. The minimum oxygen intensity Io in the oxygen intensity reduction region min The maximum oxygen intensity Io in the region outside the oxygen intensity reduction region. max The ratio of Io min / Io max The value ranges from 0.85 to 0.
96.
2. The directional electromagnetic steel plate according to claim 1, characterized in that, The oxygen intensity reduction region exists at intervals L of 5–30 mm.
3. The directional electromagnetic steel plate according to claim 1 or 2, wherein, The chemical composition of the base steel plate, expressed as a percentage by mass, contains one or more elements selected from the following: Ni: 0.01~0.50%, Cu: 0.01~0.50%, Sb: 0.01~0.30% Sn: 0.01~0.30% Cr:0.01~0.50%、 P:0.01~0.05%、 Mo: 0.01–0.05% Ta: 0.01~0.05% Nb: 0.001~0.010%, V:0.01~0.50%、 B:0.001~0.010%、 Bi: below 0.0150%, and Te: below 0.0150%.
4. The directional electromagnetic steel plate according to claim 1 or 2, wherein the plate thickness is 0.15 to 0.23 mm.
5. The directional electromagnetic steel plate according to claim 1 or 2, wherein, The thickness of the base steel plate is 0.14 to 0.22 mm.
6. A method for manufacturing a directional electromagnetic steel plate, characterized in that, It has the following processes: A hot rolling process involves heating a slab and then hot rolling the heated slab to produce a hot-rolled steel plate. The slab contains, by weight percent: Si: 2.50~4.00% Mn: 0.01~0.30%, N:0.0030~0.0150%、 C:0.010~0.100%、 sol.Al: 0.010~0.050%, Selected from one or more of S and Se: total 0.010–0.050%, Ti: 0.001–0.010%. Ni: 0~0.50%, Cu: 0~0.50%, Sb: 0~0.30%, Sn: 0~0.30% Cr:0~0.50%、 P:0~0.05%、 Mo: 0–0.05%, Ta: 0~0.05%, Nb: 0~0.010%, V:0~0.50%、 B:0~0.010%、 Bi: 0~0.0200%, and Te: 0~0.0200%, The remaining portion contains Fe and impurities; The hot-rolled steel sheet is annealed using a hot-rolled sheet annealing process. The cold rolling process involves cold rolling the hot-rolled steel sheet after the annealing process to produce a cold-rolled steel sheet. The decarburizing annealing process of decarburizing annealing the cold-rolled steel sheet to produce decarburized annealed steel sheet; The finished annealing process involves coating the decarburized annealed steel sheet with an annealing separating agent and then performing finished annealing to form a primary coating on the surface of the decarburized annealed steel sheet, thereby producing a finished annealed sheet; and The insulating film forming process involves forming an insulating film on the surface of the finished annealed plate. The total reduction rate in the cold rolling process is over 89%. The decarburization annealing process includes the following steps: A localized heating process in which the surface of the cold-rolled steel sheet is partially heated in an atmospheric atmosphere by laser beam irradiation at intervals of 5 to 30 mm in a direction at an angle of 30 to 150° relative to the rolling direction. The process of heating the cold-rolled steel sheet after the local heating process from a temperature range below 450°C to a decarburization annealing temperature range of 750-950°C in a non-oxidizing atmosphere at an average heating rate of 80°C / second to 2000°C / second. and The cold-rolled steel sheet after the heating process is subjected to an oxygen potential P that satisfies the following formula (1). O The homogenization process is carried out for decarburization annealing. Under the irradiation conditions of the laser beam during the local heating process, the average intensity of the laser beam, expressed in W, is set as P; the focusing diameter of the focused spot in the rolling direction, expressed in mm, is set as Dl; the focusing diameter of the focused spot in the width direction orthogonal to the rolling direction, expressed in mm, is set as Dc; the irradiation time, expressed in sec, is set as t; and the instantaneous input energy, expressed as 4 / π×P / (Dl×Dc)×t, is set as J / mm². 2 When the setting is Up, the following equation (2) is satisfied. P O ≤0.6-0.04Up (1), 1≤Up≤5 (2)。 7. The method for manufacturing a directional electromagnetic steel plate according to claim 6, wherein, The chemical composition of the slab, expressed as a percentage by mass, contains one or more elements selected from the following: Ni: 0.01~0.50%, Cu: 0.01~0.50%, Sb: 0.01~0.30% Sn: 0.01~0.30% Cr:0.01~0.50%、 P:0.01~0.05%、 Mo: 0.01–0.05% Ta: 0.01~0.05% Nb: 0.001~0.010%, V:0.01~0.50%、 B:0.001~0.010%、 Bi: below 0.0100%, and Te: below 0.0100%.
Citation Information
Patent Citations
Production of grain oriented silicon steel sheet excellent in magnetic property
JP1994145799A
Production of grain oriented silicon steel sheet having extremely low iron loss
JP1995062438A
Vehicle drive device
JP2023065018A